Development of brain signal processing interface software for Trackit-LabVIEW - Ramli, R.; Mokhtar, Norrima; Arof, Hamzah; Mohd Anwar, M.S.; Meor Hamzah, N.H.; Ibrahim, Fatimah (2009)
There are many digital electroencephalography (EEG) acquisition systems available nowadays for researchers due to the demand in the brain signal research. The electroencephalography (EEG) acquisition systems varied on the specification, design and prices. One of the ambulatory amplifiers for acquisition is the Trackit from Lifelines Limited. Presently, the Trackit system is only available for clinical applications. In order to integrate from clinical applications to research capabilities, the Trackit has to be interfaced with software that be able to do the electroencephalography (EEG) signals processing. In our project, Lab VIEW is chosen as our software platform. Therefore, we have taken the initiative to developed the software for Trackit-Lab VIEW interfaced. In this paper, we have demonstrated that the acquired electroencephalography (EEG) signals obtained using TrackitLab VIEW software. Example of signal processing application on the raw electroencephalography (EEG) signals was shown in the results section.